Power Engineering Development Programme of Federal Government of Germany up to 2050 – Basis of Sustainable Ecological Development - W. Risner; V. N. Nagornov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a long-term programme for power engineering development in Germany and its specific features, namely: development of power generation on the basis of renewable sources, consistent decommissioning of Nuclear Power Plants, reduction in energy consumption due to higher efficiency of its usage, reduction in greenhouse gas emissions.